The Waqf Bank .. An original jurisprudential study Among the publications of Dar Konoz Eshbelia for Publishing and Distribution. : Origin of the book: An academic thesis submitted for PhD in jurisprudence, from the College of Sharia in Riyadh at Imam Muhammad bin Saud Islamic University. (مجلة وقف في دراسات الاوقاف, 2026)
The endowment bank is: an idea for a banking institution that holds capital, distributing profits, and it is a new addition in contemporary endowment forms and in the Islamic commercial banking system, and is considered a banking alternative that performs its economic and social role efficiently through legitimate financing methods to achieve the desired purposes.  The endowment bank includes a number of characteristics that distinguish it from other banks in terms of: achieving justice and real economic growth, and it is an important tributary to the State's social and economic developmental work. It also, carries out banking and investment activities recognized in commercial banks in a way that does not conflict with the provisions of the endowment, and does not contradict the statute of the endowment bank considered as the conditions of the endowers in terms of following its rules.  The shareholder in the bank is the dower, the bank's capital is the endowment, and the beneficiary of the bank's profits is the recommended by the dower. There is no legal objection to the endowment bank to take the form of a joint stock company, as required by the regulations, and its incorporation is allowed, exteriorization on authenticity of monetary endowment. It is considered one of the legitimate forms of collective endowment. It has internal and external financial resources, the internal: its capital, its reserves, and the external: deposits, and donations. And it may take precautions by graduating from the agreement of the jurists on the legality of endowment architecture, restoring it, reforming it, and doing what it preserves, and the external: deposits, and donations.